2009
DOI: 10.1192/bjp.bp.109.067082
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ischaemic heart disease and stroke in individuals with psychosis under universal healthcare

Abstract: People with a history of psychosis do not receive equitable levels of vascular care under universal healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 35 publications
11
95
3
2
Order By: Relevance
“…18,[91][92][93] They are also less likely to receive appropriate medications on discharge such as beta blockers and statins. 94 The results are consistent with findings from ambulatory and primary care where patients with severe mental illness were less likely to be assessed or treated for hyperlipidaemia. 95,96 The few exceptions to these findings are in highly specific groups such as patients of Veterans Affairs.…”
Section: Effect Of Mental Illness On Physical Health Caresupporting
confidence: 85%
“…18,[91][92][93] They are also less likely to receive appropriate medications on discharge such as beta blockers and statins. 94 The results are consistent with findings from ambulatory and primary care where patients with severe mental illness were less likely to be assessed or treated for hyperlipidaemia. 95,96 The few exceptions to these findings are in highly specific groups such as patients of Veterans Affairs.…”
Section: Effect Of Mental Illness On Physical Health Caresupporting
confidence: 85%
“…Further research could establish whether patients given community treatment orders are more likely to receive appropriate care, because patients with psychiatric disorders are less likely to re ceive guideline-consistent management of physical illness. 4,6,24,25 …”
Section: Resultsmentioning
confidence: 99%
“…Using data from APPROACH, extent of coronary disease was assessed using 3 different measures: 1) left ventricular ejection fraction (LVEF); 2) the Duke Jeopardy Score, which encompasses both the percentage of stenosis in a coronary lesion and the volume of myocardium at risk (the Duke Jeopardy Score has been validated in the APPROACH population and has been shown to provide independent prognostic information in people with ischemic heart disease) [9,10]; and 3) a categorical assessment of coronary anatomy risk, with high risk anatomy defined as 3-vessel disease, left main disease, or 2-vessel disease involving the proximal left anterior descending coronary artery per the Duke Coronary Index.…”
Section: Clinical and Outcome Variablesmentioning
confidence: 99%
“…Previous research has shown that people with schizophrenia are less likely to undergo cardiac catheterization, percutaneous coronary intervention (PCI), and coronary artery bypass grafting (CABG) relative to those without schizophrenia [9][10][11][12]. Factors such as cardiac surgeon selection bias [13], socio-economic barriers [14], and informed consent issues [6] have been postulated as possible causes for this discrepancy.…”
Section: Introductionmentioning
confidence: 98%